If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4)(-2x + 6) = 0 Reorder the terms: (-4 + 3x)(-2x + 6) = 0 Reorder the terms: (-4 + 3x)(6 + -2x) = 0 Multiply (-4 + 3x) * (6 + -2x) (-4(6 + -2x) + 3x * (6 + -2x)) = 0 ((6 * -4 + -2x * -4) + 3x * (6 + -2x)) = 0 ((-24 + 8x) + 3x * (6 + -2x)) = 0 (-24 + 8x + (6 * 3x + -2x * 3x)) = 0 (-24 + 8x + (18x + -6x2)) = 0 Combine like terms: 8x + 18x = 26x (-24 + 26x + -6x2) = 0 Solving -24 + 26x + -6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + 13x + -3x2) = 0 Factor a trinomial. 2((-3 + x)(4 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {3, 1.333333333}
| a-7=25 | | -2d^2+2d+40=0 | | 3w^2=-2w+4 | | a=4+(n-1)(-3) | | 6=3x+3 | | -6d+6d= | | 6(c-4)=c+2 | | 4x+2(1.5-2x)=3 | | 3(n-5)=21 | | 21x-24=9x+24 | | -3(-10+2x)=-42 | | -3(7x+10)=-30 | | 6(2+7x)=-72 | | X-12=8x-6 | | 5(-8+4x)=-180 | | 6(5x+4)=-156 | | 5(9-5x)=-230 | | 6(-7+3x)=156 | | 2x^2=1-x | | 7x^2-3.2x=2 | | -7(2x+1)=105 | | x^2-10x+2=0 | | 3(6+6x)=72 | | 3(6+6x)=62 | | 5(6+x)=65 | | (7x+8)-(2x-8)= | | a+12=-33 | | Y=2+0.25x | | 5x+13x=72 | | 0.3(3.3)-y=0 | | 6s-5t+2s+2t= | | 0.3x-y=0 |